POTRET PEREMPUAN DI DUNIA MAYA - Sartana Sartana (Kafa`ah: Journal of Gender Studies, 2014)
The number of internet users fewer females than males, internet brings many benefits for women. Internet helps reconstruct people's views about gender. High encourage women to have equal footing with men; facilitate women to engage in activities in the context of the public sphere, has space for mengaktualisaikan themselves, as well as an opportunity  to  live  more  independently.  On  the  other  hand,  the Internet also raises new problems for women. Internet often becomes a medium for the occurrence of crime and violence against women. Such forms of violence in the form of a message containing the anger and hatred, harassment, threats, fraud, use of false identities, or stalking. From the description, it is necessary encouragement and support for women in order to use the Internet in a healthy and productive. In addition, women also need to be protected from various threats while interacting in the virtual world.  Keywords: cyberspace, gender, womanCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.101